The Model of People’s Participation in Crime Prevention in Hiranruchi Sub-district, Thonburi District, Bangkok - Nareenoi, Phongphan; Seangyai, Kanyanat; Charoensheep, Jariyaporn (Rajapark Journal, 2023)
The purpose of this research was to study, compare, analyze the relationship of stakeholders in a community project of Thonburi district and present a form of participation of people in the target area. The sample consisted of 382 people, 36 key informants, and 5 experts. Data were collected from questionnaires and interviews and analyzed by using frequency, percentage, mean, standard deviation, t-test, F-test, Pearson’s correlation coefficient. statistics. Content based information was also analyzed. The results showed that participation in participating in the overall project was low, while participations in topics of crime prevention and safety management were moderate. Subjects with different sex and education showed their opinions indifferently on participation in the project. The sample groups with different age, marital status, occupation and income expressed different opinions on participation in the project. The samples with different gender, age, marital status, education, occupation and income had different opinions on participation in crime prevention topic. The samples with different levels of education showed indifferent opinions on safety management participation. the sample group with different gender, age, marital status, occupation and income had different opinions on security management topic. Participation in participating the project and topics of crime prevention had positive correlation with safety management at a statistical significance level of 0.05. The form of participation was assessed and certified as a good form to be applied for further use in real situations.